Harlan Fiske Stone papers - Stone, Harlan Fiske, 1872-1946.
Correspondence, writings, reports, legal case files, biographical information, and other papers relating primarily to Stone's service on the U.S. Supreme Court. Also reflects Stone's work as trustee of Amherst College, chairman of its committee on the Folger Shakespeare Library, chairman of the board of trustees of the National Gallery of Art (U.S.), chancellor of the Smithsonian Institution, and dean and professor in the Columbia University Law School.
Includes correspondence of Alpheus Thomas Mason, Stone's biographer, which contains reminiscences of Stone by such persons as Irving Brant and Mabel Walker Willebrandt. Family correspondents include Stone's sons, Marshall Harvey Stone and Lauson Harvey Stone; his brother, Lauson Stone; and his sister, Helen Luthera Stone Willard. Other correspondents include Charles C. Burlingham, Nicholas Murray Butler, Sterling Carr, William O. Douglas, John Foster Dulles, Felix Frankfurter, Learned Hand, Herbert Hoover, Charles Evans Hughes, John Bassett Moore, Owen J. Roberts, Luther Ely Smith, Young Berryman Smith, and George Sutherland.
U.S. attorney general, associate and chief justice of the U.S. Supreme Court, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brant, Irving, -- 1885-1976.; Burlingham, Charles C. -- 1858-1959 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Carr, Sterling, -- 1876- -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Hand, Learned, -- 1872-1961 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Mason, Alpheus Thomas, -- 1899-1989 -- Correspondence; Moore, John Bassett, -- 1860-1947 -- Correspondence; Roberts, Owen J. -- 1875-1955 -- Correspondence; Smith, Luther Ely, -- 1873-1951 -- Correspondence; Smith, Young B. -- 1889-1960 -- Correspondence; Stone, Lauson, -- 1883-1948 -- Correspondence; Stone, Lauson Harvey, -- 1904-1999 -- Correspondence; Stone, Marshall H. -- 1903-1989 -- Correspondence; Sutherland, George, -- 1862-1942 -- Correspondence; Willard, Helen Luthera Stone, -- 1886- -- Correspondence; Willebrandt, Mabel Walker, -- 1889-1963.; United States. -- Department of Justice. -- Office of the Attorney General; United States. -- Supreme Court; Amherst College; Columbia University. -- School of Law; Folger Shakespeare Library; National Gallery of Art (U.S.); Smithsonian Institution; Art museums -- Washington (D.C.); Constitutional law -- United States; Law -- United States; Law schools -- New York (State) -- New York; Libraries -- Washington (D.C.); Museums -- Washington (D.C.); Universities and colleges -- Massachusetts -- Amherst; Cabinet officers; Educators; Jurists; Lawyers